Differential antiviral activity of European sea bass interferon-stimulated 15 protein (ISG15) against RGNNV and SJNNV betanodaviruses. - Moreno, Patricia; Álvarez-Torres, Daniel; García-Rosado, Esther; Borrego-García, Juan José; Alonso-Sánchez, María del Carmen (ScienceDirect, 2018)
ISG15 is an antiviral protein acting intracellularly, by conjugation to viral or cellular proteins, or extracellularly, as cytokine. In this work, an in vitro system, consisting of E-11 cells over-expressing European sea bass ISG15 (Dl_ISG15_E11 cells), has been developed to evaluate the European sea bass ISG15 protein activity against RGNNV and SJNNV isolates. Regarding RGNNV, RNA2 copy number and viral titres were similar in E-11 and Dl_ISG15_E11 cells, and the cellular survival analyses demonstrated that Dl_ISG15_E11 cells were not protected against this virus. In contrast, ISG15 compromises SJNNV replication, since a reduction of the SJNNV genome synthesis has been recorded. The ISG15 anti-SJNNV activity was confirmed by viral titration and survival assays. In addition, a role of the intracellular ISG15 in modulating the transcription of endogenous genes has being recorded, with tlr3 gene being knocked out and e3 gene being up-regulated in RGNNV-inoculated Dl_ISG15_E11 cells. Sea bass ISG15 has also been detected extracellularly, and its activity has been evaluated by co-culture. The survival rate of RGNNV-inoculated E-11 cells increased from 25% to 46% when they were co-cultured with ISG15-producing cells. Similarly, the survival rate of SJNNV-inoculated E-11 cells increased from 27% to 51% in co-culture with ISG15-producing cells. To our knowledge, this is the first description of a differential antiviral activity of an ISG15 protein against two betanodavirus species, and the first evaluation of the cytokine-like activity of a fish ISG15 protein on non-immune cells.
Keywords: Agentes antivíricos; Lubinas; ISG15; European sea bass; Betanodavirus